Diversity and Density Gastropods in Mangrove Forest of Si Runtoh Beach, Baluran National Park - Siwi, Fitri Retnananing; Sudarmadji, S.; Suratno, S. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
The mangrove forest is one of the coastal ecosystems of unique and productive. One of the animals that can be found in the mangrove ecosystem are gastropods. Gastropods constitute the largest class of the phylum of mollusks. Gastropods can usually be found in tidal areas, because these animals have a very high adaptability. The existence of mangrove gastropods in the area can be used as an indicator that the mangrove on the beach working properly or not. Diversity and density of research conducted in the mangrove forest Si Beach Runtoh Baluran National Park in February until April 2014 during a low tide maximal. The sampling method used in this research is the method of transects made per station. Transect length is 100 m, the total number of stations is 8, and the distance between the station 25 m. In one station consists of 8 transects, transects 15 m spacing, each transect consists of three plots measuring 5 m x 5 m. The results showed a diversity of mangrove Gastropods Si Beach Runtoh Baluran National Park is H '= 4,180 were classified as moderate while gastropods density obtained is 0.832 individu/m2. Keywords: gastropods, diversity, density